Physicо-chemical characterization and transport features of proton-conducting Sr-doped LaYO3 electrolyte ceramics. Issue 11 (September 2016) - Danilov, N.; Vdovin, G.; Reznitskikh, O.; Medvedev, D.; Demin, A.; Tsiakaras, P.
Abstract: Structure, thermal and transport properties of chemically stable proton-conducting La0.9 Sr0.1 YO3–δ electrolyte are investigated in the present work. The features of ceramics preparation, thermal expansion and electrical conductivity are thoroughly examined by the aid of X-ray diffraction analysis, thermogravimetry coupled with differential scanning calorimetry, scanning electron microscopy, high-temperature dilatometry and 4-probe dc-conductivity measurements. From the experimental results it is demonstrated that Sr-doped LaYO3 material can be easily prepared by citrate-combustion synthesis method. It is found that the sintered ceramic samples are highly dense and possess acceptable thermal expansion coefficients. Despite the fact that their absolute ionic conductivity level is found to be rather low, the ionic transport dominates for a wide range of oxygen partial pressures at the interval between 600 and 900 °C, suggesting the use of the as prepared LaYO3 -based materials for pumping and sensing devices.